REPEDÉSEK A TRANSZATLANTI KAPCSOLATOKBAN? A KÖZEL–KELET PÉLDÁJA - Csicsmann, László (Közép-Európai Közlemények, 2020)
This paper is aimed at analysing the impact of the crisis of the liberal international order on the transatlantic relations. Both the EU and the US have vital interest to maintain the existing international order, however regarding certain foreign policy goals we witness an increasingly divergent approach to world politics. This is the case with the Middle East, where the EU acts as a global player based on historical ties, while the United States have recently started a gradual disengagement from the region. The so-called post-American Middle East have its own opportunities as well as challenges for the European diplomacy. This article focuses on the differences between the EU and the US foreign policy goals related to the Middle East. It primarily addresses the Iranian nuclear program and the Middle East Peace Plan recently launched by the US. The author argues despite some differences in interests, the EU and the US do not perceive the region in an entirely different way.